2012
DOI: 10.4067/s0718-58392012000200018
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacteria from Pinus taeda L. as Biocontrol Agents of Fusarium circinatum Nirenberg & O'Donnell

Abstract: 1Fusarium circinatum Nirenberg & O'Donnell, the pitch canker fungus, has been recently reported in Uruguay affecting Pinus taeda L. seedlings. The spread of this pathogen to plantations constitute a risk to forestry production. The aim of this work was to evaluate the inhibitory effect of live bacteria and their thermostable metabolites on F. circinatum growth in vitro. Four Bacillus subtilis strains and one of Burkholderia sp. isolated as P. taeda endophytes were evaluated as biological control agents of F. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
3
14
0
3
Order By: Relevance
“…The current results showed that the use of different bioagents including fungal species, yeast species, and aqueous extract of bitter apple was able to inhibit the mycelial growth of B. allii-the causal pathogen of Botrytis umbel blight disease. These results were supported by other findings that approved the efficiency of many bioagents in biocontrol of plant diseases (Wang et al 2010;Soria et al 2012;). Trichoderma spp.…”
Section: Antagonistic Effects Of the Bioagents In Vitrosupporting
confidence: 85%
“…The current results showed that the use of different bioagents including fungal species, yeast species, and aqueous extract of bitter apple was able to inhibit the mycelial growth of B. allii-the causal pathogen of Botrytis umbel blight disease. These results were supported by other findings that approved the efficiency of many bioagents in biocontrol of plant diseases (Wang et al 2010;Soria et al 2012;). Trichoderma spp.…”
Section: Antagonistic Effects Of the Bioagents In Vitrosupporting
confidence: 85%
“…; Soria et al. ). The potential of Trichoderma species as biocontrol agents of plant diseases was first recognized in the early 1930s (Weindling ), and since then, there have been extensive efforts in the commercial production of them for disease control in a number of crops (Harman ; Gardener and Fravel ).…”
Section: Introductionmentioning
confidence: 98%
“…Although chemical control of onion blotch had been practised and its success depends largely on high frequency of spraying, but today, there are strict regulations on chemical fungicide use due to carcinogenic effects, residual toxicity problems, environmental pollution and development of fungicideresistant strains (Ben ıtez et al 2004;Rial-Otero et al 2005). Therefore, there are a large number of studies that have been devoted to apply a biological control as nature-friendly alternative method (Siameto et al 2010;Soria et al 2012). The potential of Trichoderma species as biocontrol agents of plant diseases was first recognized in the early 1930s (Weindling 1932), and since then, there have been extensive efforts in the commercial production of them for disease control in a number of crops (Harman 1996;Gardener and Fravel 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis and Burkholderia sp. inhibited F. circinatum growth in vitro (Soria et al ., ). Inhibition of growth of F. circinatum by strains of Micromonospora isolated from alfalfa root nodules was also reported in vitro (Martínez‐Hidalgo et al ., ).…”
Section: The Use Of Biological Control For Combating F Circinatummentioning
confidence: 97%